2006
DOI: 10.1103/physrevb.73.144502
|View full text |Cite
|
Sign up to set email alerts
|

Quantum fluctuations in Larkin-Ovchinnikov-Fulde-Ferrell superconductors

Abstract: We study the superconducting order parameter fluctuations near the phase transition into the Larkin-Ovchinnikov-Fulde-Ferrell state in the clean limit at zero temperature. In contrast to the usual normal metal-to-uniform superconductor phase transition, the fluctuation corrections are dominated by the modes with the wave vectors away from the origin. We find that the superconducting fluctuations lead to a divergent spin susceptibility and a breakdown of the Fermi-liquid behavior at the quantum critical point.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 65 publications
(82 reference statements)
2
19
0
Order By: Relevance
“…The LO phase can be generalized to higher order crystalline states with multiple plane-wave components. While a stable FFLO state may exist in an anisotropic system [8,9] or in a lattice, [9][10][11] especially in a low dimensions, [12][13][14] however, it has been shown that the FFLO states are intrinsically unstable in clean homogeneous 3D and 2D continuum systems. [15] Instead, noncondensed pairing with the lowest pair energy at finite momenta is expected, which may lead to exotic ground states.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LO phase can be generalized to higher order crystalline states with multiple plane-wave components. While a stable FFLO state may exist in an anisotropic system [8,9] or in a lattice, [9][10][11] especially in a low dimensions, [12][13][14] however, it has been shown that the FFLO states are intrinsically unstable in clean homogeneous 3D and 2D continuum systems. [15] Instead, noncondensed pairing with the lowest pair energy at finite momenta is expected, which may lead to exotic ground states.…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58] Theoretical studies have found that the FFLO states become unstable in various situations. [59][60][61] In particular, it is shown in ref. [15] that due to the inevitable pairing fluctuations (including both amplitude and phase), the FFLO states are intrinsically unstable in isotropic 3D and 2D systems, and thus exotic pairing state may emerge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the order of the phase transition between the FFLO and BCS phases is still under debate [72][73][74][75][76][77][78]. For 1D systems the studies of that problem within the framework of the Ginzburg-Landau theory show that e.g.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…It turns out that the LOFF state is also relevant for other fermionic systems with pairing instability and mismatched Fermi surfaces, e.g., cold atomic Fermi gases 4 and "color superconducting" quark matter. 5 While most theoretical studies have focused on the phase diagram and the structure of the order parameter in the LOFF state, a number of recent works looked at thermal or quantum fluctuations [6][7][8][9] and topological defects, such as vortices and dislocations. 6,[10][11][12] According to the Goldstone theorem, spontaneously broken continuous symmetry results in gapless bosonic excitations.…”
Section: Introductionmentioning
confidence: 99%